Level of satisfaction and correlation between the performance and self-evaluation of physical therapy students in the objective structured clinical examination (OSCE) when using physical agents - Hernán Andrés de la Barra-Ortiz; Luis Adrián Gómez-Miranda; Juan Ignacio de la Fuente-Astroza (Revista de la Facultad de Medicina)
Introduction: Objective structured clinical examination (OSCE) is a validated instrument that allows measuring clinical skills in health sciences students; thus, it is important to know the students’ level of satisfaction with this strategy, as well as the correlation between performance and self-evaluation.